934 Chemical Burns and the Use of High-Strength Topical Lidocaine Cream in Tattooing - a Case Report. (19th August 2022) - Noton, T; Burke-Smith, A; Jones, I
Abstract: Topical anaesthetics have long been used for their ease of use and short duration to provide local anaesthetic prior to procedures such as cannulation and tattooing. We present the case of a 26-year-old tattoo artist sustaining a chemical burn and resulting infection from a high-strength topical lidocaine cream. The patient presented to the emergency department 5-days following application of the cream. The topical preparation was sourced online, came in a nondescript white tube, and was marketed as having a 50% lidocaine content with no information regarding its constitution. For comparison, EMLA cream (lidocaine/prilocaine) commonly used in hospitals, is a 5% preparation. Following application, the patient proceeded to self-tattoo his left lower leg, in a 'blackout' style. On presentation, a 2.5% TBSA area was blistered, with areas of denuded skin, in keeping with a deep dermal burn. Much of the lower leg was actively discharging yellow-stained serous fluid. In addition, there was tracking erythema around the demarcated area, and the left foot was grossly oedematous. Blood tests revealed CRP of 103 and WCC of 11.4. The patient was commenced on intravenous flucloxacillin. Wound swab results showed significant growth of Pseudomonas aeruginosa . Following stepdown to oral antibiotics and careful wound management with dressings such as Flaminal and then honey-based dressings, the patient made a full recovery, avoiding the requirement for surgical intervention. This case highlights the difficulty when assessing burns in heavily tattooed skin. Additionally, unregulated topical anaesthetics must be avoided by the public, due to infection risk and unknown ingredients.